Selected risk factors of infertility in women: case control study - M., Mallikarjuna; V., Rajeshwari B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Infertility implies apparent failure of a couple to conceive. If a couple fails to achieve pregnancy after one year of unprotected intercourse, it is an indication to investigate the couple. This is based on the observation that, 80% of the normal couples achieve conception within a year. Methods: A case control study on the selected risk factors of female infertility among fifty females attending the Tertiary care centre was conducted. The data was collected from fifty cases and fifty controls, matched for age, using a pre-structured questionnaire. The data collected included menstrual details, uterine or ovarian disorders, genito-urinary infections, systemic illness, hyperprolactinemia and weight gain. Data was analysed to find out risk factors and its association using Odds ratio, chi-square and logistic regression. Results: The factors include age, duration of menstrual cycles, dysmenorrhea, Hyperprolactinemia, recent weight gain, body mass index (BMI), ovarian dysfunctions, thyroid disorders and uterine abnormalities. Conclusions: Early screening and diagnosis of menstrual disorders and diseases like hyperprolactinemia, Thyroid disorders, uterine abnormalities, ovarian dysfunctions and correcting them by appropriate treatment.